Users’ perceptions on Poly.AI: A qualitative study into students’ and teacher’s experiences - Halim, Abdul; Hafidh, Irfan (Acitya: Journal of Teaching and Education, 2024)
As artificial intelligence (AI) is being used more and more, thus in order to prevent exploitation, we need to be able to use and deploy it as efficiently as possible. An artificial intelligence program called a chatbot can mimics human speech and writing. Chatbots may be integrated into the field of education when utilized properly by educators and students. This study investigate the perception of teachers and students of MAN 1 Samarinda of the Integration of Poly.AI in educational practices. The purpose of this study is to investigate how high school teacher and students perceive Poly.AI in education. This study employs a Qualitative approach with in-depth interview as its research instrument. The obtained data is analyzed using thematical coding to discover the theme and topic related to answer the researchers question, such as how teacher and students precieve Poly.AI in terms of usability, effectiveness, learning experience, and what challenges they encounterd while using Ploy.AI during educational practices. The research is expected to contribute to the on going disccusion of how AI in general could affect and improved the educational field in digital era. In general the integration of Poly.AI has been well percieved by teachers and students in MAN1 Samarinda and proven to be an effective and entertaining study and teaching tools, as it could assist teacher deliver role-play related topics and help students improved them self in English.